Impact of Polymeric Solutions Parameters on Morphological Properties of Composite Nanofibers. (Journal of University of Babylon for Engineering Sciences, 2021)
The aim of this mini review article, discussed the recent research in the field of polymer nanocomposite deals with properties of polymer solution parameters such as viscosity, molecular weight, concentration of polymeric substance in solution and surface tension of solution on morphological properties of nanofibers produced by electrospinning technology such as nanofiber diameters and the number and size of beads formed on the surface of the nanofiber web. All researches have proven that the viscosity or concentration of the polymer solution, lead to  increase the diameters of the nanofibers and reduces the size and number of beads, as well as converting the fiber path jet from unstable and unmonotonous to more stable. This behavior positively affects the formation and orientation of the fibers, but did not lead to the enhancement of the crystalline and thermal properties of the nanofibers. Therefore, other researchers studied adding nanoparticles such as salts to polymeric solutions to get rid of the number and size of beads in the nanofiber web as a result of using low concentrations. These nanoparticles improve the morphological properties as well as enhance the crystalline and thermal properties of the nanofiber network, leading to increased engineering and medical applications such as wastewater treatment and drug delivery.